Hubungan antara Penggunaan Metode Pembelajaran Interaktif dengan Keaktifan Siswa pada Mata Pelajaran Pendidikan Agama Kristen dan Budi Pekerti di SMP Negeri 12 Palangka Raya - Helena Regalia Ujabi; Richard Majefat (Jurnal Pendidikan Agama dan Teologi, 2026)
Student activity is an essential parameter for evaluating success in the educational process, especially in all materials related to Christian Religious Education and Character Education. However, in practice, there are still students who are less active in participating during learning sessions. One factor that may influence this situation is the implementation of interactive learning methods. This study focuses on analyzing the relationship between the use of interactive learning methods and the level of student participation in Christian Religious Education and Character Education lessons at SMP Negeri 12 Palangka Raya. For this study, a quantitative approach was used with a correlational design. The population studied included all seventh-grade students taking Christian Religious Education and Character Education subjects, with a sample of 12 students taken through a total sampling technique. Data were collected using questionnaires, observation, and documentation. The data analysis process included testing validity, reliability, normality, linearity, and Pearson Product Moment correlation tests conducted with IBM SPSS software. It is hoped that the results of this study can provide an understanding of the relationship between the use of interactive learning methods and student participation, as well as become a consideration for educators in choosing teaching methods to increase student engagement.